TO BE ABLE TO ANALYZE AND INTERPRET THE ARTISTIC VALUE OF COMPOSITION IN WORKS OF FINE ARTS AND TO INCREASE STUDENTS’ KNOWLEDGE OF ARTISTIC PERCEPTION. - Abdimuminov Muhammad Sodiq (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
It is a responsible task for the science of pedagogy to master the concept of fine arts without lagging behind its modern examples, to share it with students and young people, and, of course, to solve this problem. In this context, the problems and requirements of the pedagogy of fine arts, including the focus on the scientific study of the theoretical foundations of fine arts as much as possible.